The New Caledonia independence referendum: What happens now? - Lee Duffield (Asia Pacific Network, 2019)
This article gives an interpretative treatment of the historical record, from France taking possession of New Caledonia in 1853, through to the current Matîgnon process, assessing indications for coming developments. Focused on the debate over independence, it considers: interests of the French state as both arbitrator and participant in events; relations among the indigenous Melanesian Kanaks, European French Caldoches, and smaller ethnic communities; memories of colonial exploitation obstructing progress; the large nickel industry; immigration, and associated minority status of Kanak society—a central problem. It describes the alternation of left and right-wing parties in government in France, with Socialist Party governments commencing moves towards independence, possibly in association with France, and conservative governments moving to countermand those moves. It posits that the parties in New Caledonia have improved their chances of finding a positive outcome through jointly participating in government during 30 years of peace.